(untitled) (Fiep Bulletin - online, 2012)
This article relates the analysis of the factors that influence the performance of pupils enrolled in elementary schools of the state public schools in Alagoas. The objective was to reflect on the failure of such school students, taking as categories of analysis the fragmentation of knowledge and practice of irregular school physical and recreational activities. It is a literature review which systematizes convergent ideas of theorists such as COLL (2000); DARIDO (2004); Zabala (1998); WALLON (1998), among others, argue that the interrelationship between school knowledge and regular activities physical and recreational activities as important factors to the development of cognitive or intellectual, motor, balance and personal autonomy (social-emotional) of the subject, allowing its full development. Studies indicate that the interrelation between school knowledge in an interdisciplinary teaching practice and regular physical activity are aspects that directly contribute to the minimization of failure school, located especially among elementary school students from public schools in Alagoas state . Expected to be, with this work, contributing to reflection on the organization of pedagogical practice and, consequently, for the minimization of that school failure.